CFD study on the performance of oxygen lance of partial combustion unit at direct reduction plant - Mohd Irwan Shah, Md Zain (2010)
Direct Reduction Plant (DRP) is one of the most important components in iron and steel making process. The performance of the DRP is very much dependent upon the heat generation by the partial oxidation process to remove oxides inside the iron ore; which the process takes place at the Partial Combustion Unit (PCU). This unit is located between the process gas heater and the oxides removal reactor. The unit consist of a transfer line, and two oxygen lances with nozzle attached to each of the lances. Turbulence flow can help the unit achieve higher operating temperature. Of course the performance of the PCU can be assessed experimentally but that require expensive experimental setup. Alternatively, the same study can be performed via Computational Fluid Dynamics (CFD) at lower cost. This study aims to increase the performance of the PCU by evaluating the various designs by mean CFD. Two different lances design were evaluated in this work along with variation in operation configuration. The modelling of turbulence flow were realised via k-e model whereas the combustion process were modelled using the species transport with eddy dissipation model. Predictions from CFD model were found to be in good agreement about 10% difference to the experimental data obtained from experimental work. This study also reveal an improvement opportunity of the PCU design as much higher temperature are achievable when wings attached to the lances to induce turbulence flow. This modelling exercise has demonstrated a cost effective route of design optimisation for PCU and hence should be used as tool for troubleshooting a design in future.